A SYSTEMATIC REVIEW: EXPLORATION OF PROCESS ANALYTICAL TECHNOLOGY TECHNIQUES (PAT) AND THEIR MULTIFACETED ADVANTAGES IN INDUSTRIAL PROCESSES - SEENIVASAN, RAAGUL; PACHIYAPPAN, JEY KUMAR; VIVEK REDDY, MURTHANNAGARI; GANESH, GNK (International Journal of Applied Pharmaceutics, 2024)
FDA initiated the PAT technology framework in the year of 2004 with the guidelines of “A framework of innovative pharmaceutical development, manufacturing and quality assurance. With that, the International Council for Harmonisation has also initiated continuous process verification to overcome the limitations of traditional methods and improve the understanding of the process and quality of the product throughout the product lifecycle. Since the year of implementation, the advancement of analytical and chemometric tools has evolved to deliver consistent quality products by understanding their process and product performance. However, the pharmaceutical industry was lacking in this technicality and implementation of highly regulated specifications. To this respect, we have stated some of the PAT tools, including NIR, Raman and Terahertz spectroscopy, as they will transfer to the futuristic prospects of analyzing the drug product with non-destructive, improved process understanding, real-time monitoring, and enhanced data integrity. This review article emphasizes the importance of PAT technology with different monitoring processes with their historical background and regulatory framework. Special attention was given to strategies, challenges, opportunities, and the compatibility of PAT tools with data fusion. Further, this will give a high-priority disciplinary scientific topic to Pharma 4.0.